KAJIAN BANJIR BANDANG DI PADANG PANJANG MELALUI TINJAUAN PETA SUNGAI - Yanto, Andri; Efendi, Efendi; Amarullah, Taufik Abdul Hasan; Putra, Dino Adi; Hardewiyani, Titik; Oktamalasendi, Unik (Jurnal Manajemen Pendidikan, 2024)
The second flash flood in Ten Koto District, Tanah Datar Regency occurred in the same place in Lembah Anai Village. The large water discharge and high flow speed caused the river to overflow and worried the residents living around the river. This was due to the very high intensity of rain in the river catchment area of ​​Lembah Anai Village which fell an hour earlier. This flash flood condition is a historic phenomenon because this is the second time. The first flash flood occurred in the Anai Valley. In 1892, the Anai Valley was also hit by a major flood. This research uses a quantitative descriptive method by making a comparative study of rivers in the Sepuluh Koto District area. The research results show that the river morphology in Lembah Anai Village has the highest catchment area of ​​400 meters above sea level (MDPL), which is the widest of the surrounding rivers and decreases in the downstream area of ​​20-meter MDPL. The highest order of average bandang potential scores is first, namely the Lembah Anai Village River, second to the Kayutanam Village River, and third to the Sicincin River. The disruption of transportation routes disrupted food supplies. Ingredients such as vegetables, potatoes and meat cannot be sent through the Anai Valley. As a result, all foodstuffs in the cities of Padang and Bukittinggi experienced price increases for months because reconstruction efforts were long and expensive.